A new 17 X-STR multiplex for forensic purposes. (December 2015) - Prieto-Fernández, Endika; Baeta, Miriam; Núñez, Carolina; Jiménez-Moreno, Susana; de Pancorbo, Marian M.
Abstract: The use of STRs located in the X chromosome (X-STRs) is very efficient for determining kinship between fathers and daughters as well as other complex kinship cases. Currently, X-STR markers are analyzed by using two different multiplexes, the decaplex of the GHEP-ISFG and the Investigator Argus X-12 Kit. Here, we present a new multiplex whose advantage is the analysis of 17 X-STRs in a single reaction. Population samples from four different continents were analyzed. A sensitivity test showed the efficacy of this new multiplex for samples with DNA quantities as low as 100 pg.